Defining Forest for Conservation and Socio-Economic Development of India - Vasudeva, S. P. (Indian Forester, 2016)
There is no clear and comprehensive definition of the term forest in Indian Forest Act, 1927 or any other legislative tool of the country. Accordingly, attempt has been made to define forest based on what is contained in various dictionaries and encyclopedia, functions these perform, what is contained in various Acts related to forests and forestry in India and work being undertaken by Forest Survey of India. The different aspects taken into account by various countries and Multi-lateral organisations while defining forest has also been considered. The definition thus arrived at is based on canopy cover/density and height of trees along with nature of species contained in that area of land. Such a definition of forest would help in conservation of forests, utilizing their socio-economic as well as environmental potential, in tackling the menace of climate change and other environmental hazards. It will take us towards fast track socioeconomic development of the country which sometimes gets hindered due to faulty understanding and interpretation of the term forest and its application due to regulatory Forest Acts.